2014
DOI: 10.1111/cpr.12125
|View full text |Cite
|
Sign up to set email alerts
|

In vitro combined treatment with cetuximab and trastuzumab inhibits growth of colon cancer cells

Abstract: Targeting EGFR and HER-2 simultaneously could have useful applications in colorectal cancer treatment. To improve pharmacological efficacy of cetuximab and trastuzumab combination, molecular mechanisms involved in their activity need to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Among the proposed mechanism of action of this agent, ADCC is suggested as a major mechanism of trastuzumab-mediated tumor cell death [ 37 , 38 ]. Further, HCT116 cells have previously been reported to express HER2 receptor [ 39 ] and trastuzumab-mediated HER-2 inhibition failed to block HCT116 cell proliferation [ 40 ]. Therefore, HCT116-derived cells were exposed to trastuzumab and effector cells, and target cell death was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Among the proposed mechanism of action of this agent, ADCC is suggested as a major mechanism of trastuzumab-mediated tumor cell death [ 37 , 38 ]. Further, HCT116 cells have previously been reported to express HER2 receptor [ 39 ] and trastuzumab-mediated HER-2 inhibition failed to block HCT116 cell proliferation [ 40 ]. Therefore, HCT116-derived cells were exposed to trastuzumab and effector cells, and target cell death was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…[117][118][119] Preclinical studies revealed that HER2 amplification might compensate for EGFR blockade, and combined targeting of HER2 and EGFR inhibited tumor cell proliferation, producing an effect that was stronger than that achieved using either single agent alone. 115,118,120 Several clinical trials have been developed to determine whether targeted agents against HER2positive CRC (determined by immunohistochemistry (IHC), fluorescence in situ hybridization (FISH), or chromogenic in situ hybridization) can be as effective as those against breast cancer or gastric cancer. A few of these studies using a single HER2-targeted agent, CRC colorectal cancer, mCRC metastatic colorectal cancer, PI3K phosphoinositide 3-kinase, AKT protein kinase B, also known as PKB, mTOR mammalian target of rapamycin, MEK mitogen-activated protein kinase, EGFR epidermal growth factor receptor, HER2/3/4 human epidermal growth factor 2/3/4, MAPK mitogenactivated protein kinase, STAT3 signal transducer and activator of transcription 3…”
Section: The Egfr-related Pathwaymentioning
confidence: 99%
“…When combined with the tyrosinekinase inhibitor gefitinib, the anti-tumor effect of cetuximab was augmented in colon cancer cell lines (59). The combination of cetuximab and trastuzumabled to inhibition of cell proliferation in colon cancer cells in a time-and dose-dependent manner and was associated with abnormal copy numbers of the EGFR gene (60). Cetuximab-conjugated gamma-poly (glutamic acid)-docetaxelnanomedicines induced cell death of HT-29 cells by enhancing cell cycle arrest in the G2/M phase compared to therapy without cetuximab conjugation (61).…”
Section: Cetuximab Efficacy and Resistance In Crc Treatment: Mechanismsmentioning
confidence: 99%